Técnicas de lectura comprensiva para el mejoramiento del vocabulario de los estudiantes de quinto grado de educación básica de la escuela Lauro Damerval Ayora nro.2, del cantón y provincia de Loja período académico 2014-2015 - Galvez Manchay, Carmen Graciela (2016)
This research paper entitled, techniques for improving reading comprehension vocabulary of fifth- grade of elementary school education Lauro Damerval No.2 Ayora, the canton and province of Loja academic period 2014-2015, aimed overall, applying techniques that enabled improving reading comprehension vocabulary, students in fifth year of parallel Basic Education "a" of the School of Basic Education Lauro Damerval Ayora No. 2. This research was pre - experimental also worked with using the deductive and inductive methods; techniques as the survey was aimed at both the teacher and the 17 students. Of which was evident poor knowledge of the techniques of reading comprehension and the limited vocabulary; thus it concludes that the implementation of comprehensive reading techniques made to students through workshops intervention, could make these techniques will improve their reading comprehension vocabulary